Secrets of aboriginal healing : a physicist's journey with a remote Australian tribe - Holz, Gary, 1950-2007.; Holz, Robbie, 1954- (Rochester, Vermont : Bear & Company, 2013)
"A guide to the 60,000-year-old healing system of the Aborigines revealed through one man's journey to overcome multiple sclerosis"--
Prologue : a single step -- The Outback -- Connectedness -- Willingness -- Awareness -- Acceptance -- Empowerment -- Focus -- Operating manual -- A new program -- Spirit guides -- Love and forgiveness -- Epilogue.
Keywords: Aboriginal Australians -- Health and hygiene; Aboriginal Australians -- Medicine -- History; Multiple sclerosis -- Alternative treatment; Spiritual healing -- Australia; Australian